What it takes: Evidence from a nutrition- and gender-sensitive agriculture intervention in rural Zambia - Kumar, Neha; Nguyen, Phuong Hong; Harris, Jody; Harvey, Danny; Rawat, Rahul; Ruel, Marie T. (Routledge, 2018)
The Realigning Agriculture for Improved Nutrition (RAIN) project was designed to address child undernutrition through a multisectoral approach which integrated agricultural diversification to improve access to nutritious foods, the promotion of gender equality and women’s empowerment and nutrition behaviour change communication to improve infant and young child feeding (IYCF) knowledge and practices. This paper presents the intention-to-treat impacts of the RAIN project on women’s empowerment, IYCF knowledge and practices and child anthropometry.